Social Psychology - Kassin, Saul M. (Cengage Learning, Inc, 2008)
Distinguished by its current-events emphasis, strong diversity coverage, and engaging connections drawn between social psychology and students' everyday lives, SOCIAL PSYCHOLOGY, INTERNATIONAL EDITION, remains one of the most scholarly and well-written texts in its field. Integrating classic and contemporary research, the text also includes comprehensive coverage of social cognition and evolutionary psychology, and features authoritative material on social psychology and the law. For this edition, Saul Kassin and Steven Fein welcome Hazel Rose Markus to the author team. As a leader and respected researcher in the study of cultural psychology, Markus has made significant contributions from her area of expertise to every chapter of this new edition